2021
DOI: 10.1186/s43058-021-00178-x
|View full text |Cite
|
Sign up to set email alerts
|

Adapting coordinated specialty care in the post-COVID-19 era: study protocol for an integrative mixed-methods study

Abstract: Background Coordinated Specialty Care (CSC) programs provide evidence-based services for young people with a recent onset of a psychotic disorder. OnTrackNY is a nationally recognized model of CSC treatment in New York state. In 2019, OnTrackNY was awarded a hub within the Early Psychosis Intervention Network (EPINET) to advance its learning health care system (LHS). The OnTrackNY network is comprised of 23 CSC teams across New York state. OnTrack Central, an intermediary organization, provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Research has shown the use of telehealth has improved patient engagement, medication adherence, and satisfaction. [1][2][3] Psychiatry is poised to benefit from telehealth because individual psychotherapy and parts of medication management can be done virtually. However, some practitioners believe telehealth interferes with rapport building, detection of nonverbal ques, continuity of care, and collection of physiological data.…”
mentioning
confidence: 99%
“…Research has shown the use of telehealth has improved patient engagement, medication adherence, and satisfaction. [1][2][3] Psychiatry is poised to benefit from telehealth because individual psychotherapy and parts of medication management can be done virtually. However, some practitioners believe telehealth interferes with rapport building, detection of nonverbal ques, continuity of care, and collection of physiological data.…”
mentioning
confidence: 99%